Overcoming neutrophil-induced immunosuppression in postoperative cancer therapy: Combined sialic acid-modified liposomes with scaffold-based vaccines - Cong Li; Lihong Wang; Kexin Zhang; Zeyu Wang; Zhihang Li; Zehao Li; Lijiang Chen (Elsevier, 2024)
Immunotherapy is a promising approach for preventing postoperative tumor recurrence and metastasis. However, inflammatory neutrophils, recruited to the postoperative tumor site, have been shown to exacerbate tumor regeneration and limit the efficacy of cancer vaccines. Consequently, addressing postoperative immunosuppression caused by neutrophils is crucial for improving treatment outcomes. This study presents a combined chemoimmunotherapeutic strategy that employs a biocompatible macroporous scaffold-based cancer vaccine (S-CV) and a sialic acid (SA)-modified, doxorubicin (DOX)-loaded liposomal platform (DOX@SAL). The S-CV contains whole tumor lysates as antigens and imiquimod (R837, Toll-like receptor 7 activator)-loaded PLGA nanoparticles as immune adjuvants for cancer, which enhance dendritic cell activation and cytotoxic T cell proliferation upon localized implantation. When administered intravenously, DOX@SAL specifically targets and delivers drugs to activated neutrophils in vivo, mitigating neutrophil infiltration and suppressing postoperative inflammatory responses. In vivo and vitro experiments have demonstrated that S-CV plus DOX@SAL, a combined chemo-immunotherapeutic strategy, has a remarkable potential to inhibit postoperative local tumor recurrence and distant tumor progression, with minimal systemic toxicity, providing a new concept for postoperative treatment of tumors.